Land use and soil organic matter in South Africa 1: A review on spatial variability and the influence of rangeland stock production - Chris du Preez; Cornie van Huyssteen; Pearson Mnkeni (South African Journal of Science)
Degradation of soil as a consequence of land use poses a threat to sustainable agriculture in South Africa, resulting in the need for a soil protection strategy and policy. Development of such a strategy and policy require cognisance of the extent and impact of soil degradation processes. One of the identified processes is the decline of soil organic matter, which also plays a central role in soil health or quality. The spatial variability of organic matter and the impact of grazing and burning under rangeland stock production are addressed in this first part of the review. Data from uncoordinated studies showed that South African soils have low organic matter levels. About 58% of soils contain less than 0.5% organic carbon and only 4% contain more than 2% organic carbon. Furthermore, there are large differences in organic matter content within and between soil forms, depending on climatic conditions, vegetative cover, topographical position and soil texture. A countrywide baseline study to quantify organic matter contents within and between soil forms is suggested for future reference. Degradation of rangeland because of overgrazing has resulted in significant losses of soil organic matter, mainly as a result of lower biomass production. The use of fire in rangeland management decreases soil organic matter because litter is destroyed by burning. Maintaining or increasing organic matter levels in degraded rangeland soils by preventing overgrazing and restricting burning could contribute to the restoration of degraded rangelands. This restoration is of the utmost importance because stock farming uses the majority of land in South Africa.